A Design Case: Assessing the Functional Needs for a Multi-faceted Cybersecurity Learning Space - Charles J. Lesko Jr. (Journal of Cybersecurity Education, Research & Practice)
Following a multi-year effort that developed not only a detailed list of functional requirements but also the preliminary physical and logical design layouts, the concept for a multi-faceted cybersecurity center was approved and the physical, as well as, additional infrastructure space was subsequently allocated. This effort briefly describes the structure and scope of the current cybersecurity program being supported and then draws out the functional requirements that were identified for the center based on the needs of the institution’s cybersecurity program. It also highlights the physical and logical design specifications of the center, as well as, the many external program delivery requirements that were identified as essential to not only the current cybersecurity program but also the projected future needs of the program and its supporting activities.